KAJIAN TEKNIS DAN EKONOMIS PEMANFAATAN KAYU PERUPUK - I M Sulastiningsih; Setiasih Irawanti; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Formerly perupuk wood was not recognized as good raw material by wood working manufacturers. Because of the increasing scarcity of ramin wood, the perupuk wood had gained the benefit of the situation as indicated by increasing demand and price of perupuk wood.The technical and economic studies on perupuk wood (Lophopetalum. spp) utilization wascarried out at one wood working mill in Gresik, East Java in 1994. The objectives of the study were to identify kind of products resulted from perupuk utilization, recovery level of each product, productivity and efficiency ofperupuk wood working machineries, and its value added.The study showed that kind of products resulted from perupuk utilization were moulding,smooth-four-side (S4S), finger jointed stick, solid jointed board and finger jointed board. The average recovery of perupuk utilization was 55% and the highest recovery (65.60%) was obtained by smooth-four-side product. The double planer machine had the highest productivity because all products used the machine to get the standard dimensions. The efficiency of some perupuk wood working machineries still low. The value added of perupuk wood working products were 90%, 55%, 52%, 37% and 24% for smooth-four-side, finger jointed board, moulding, solid jointed board and fingerjointed stick respectively.Key words : perupuk, wood working, recovery and value added.